Coincidental coronary artery disease impairs outcome in patients with takotsubo cardiomyopathy - Bill, Verena; El-Battrawy, Ibrahim; Schramm, Katja; Ansari, Uzair; Hoffmann, Ursula; Haghi, Dariusch; Kuschyk, Jürgen; Borggrefe, Martin; Akın, Ibrahim (QJM, 2017)
Background and aim: Takotsubo cardiomyopathy (TC) is an important differential diagnosis of coronary artery disease (CAD), mimicking acute coronary syndrome in clinical symptoms, biomarker profiles and ST-elevation in ECG. Absence of occlusive coronary disease is an essential criterion distinguishing both diseases. The aim of the study was to explore the influence of co-existing incidental CAD on poorer clinical outcomes and all-cause mortality in TC. Design, methods and results: Our mono-centric study cohort constituted 114 consecutive patients diagnosed with TC between 2003 and 2015. The primary endpoint was the all-cause mortality. Additionally, we compared the incidence of thromboembolic events, life-threatening arrhythmias, cardiogenic shock and in-hospital death. There was no significant difference in gender distribution or mean age in both groups. Patients diagnosed with a co-existing CAD (n = 22), had a more pronounced cardiovascular risk profile. The all-cause mortality among patients with co-existing CAD after a 2-year follow-up was higher than those diagnosed with lone TC (22.7 vs. 5.4 %, P = 0.07). In a multivariate cox regression analysis CAD (HR 3.5, 95 %CI 1.0-11.6; P = 0.04), LVEF ≤ 35% (HR 3.8, 95% CI 0.0-0.6, P = 0.01) and cardiogenic shock (HR 3.8, 95% CI 1.2-11.3; P = 0.01) were independent predictors of the primary endpoint. Conclusion: Our study reveals that co-existing CAD impairs the outcome in patients with TC. The diagnostic work-up for TC should therefore not necessarily hinge on ruling out CAD.
Published: 14 March 2017
Gesehen am 9.06.2018